Malignant lymphomas and occupational exposures. Issue 8 (August 1989) - Persson, B; Dahlander, A M; Fredriksson, M; Brage, H N; Ohlson, C G; Axelson, O
Abstract : The effects of potential risk factors for Hodgkin's disease (HD) and for non-Hodgkin lymphomas (NHL) were evaluated in a case-referent study encompassing 54 cases of HD, 106 cases of NHL, and 275 referents, all alive. Exposure information was obtained by questionnaires posted to the subjects. Crude rate ratios were increased for various occupational exposures including solvents, welding, wood preservatives, phenoxy acids, and fresh wood (sawmill workers, lumberjacks, paper pulp workers). After further analyses based on logistic regression occupational exposures to welding and creosote remained as significant risk factors for HD. For NHL, occupational exposures to solvents, phenoxy acids, and creosote but also work as carpenter or cabinet maker and contacts with pets (other than dogs, cats, and birds) were associated with significantly increased risks.